2019
DOI: 10.2174/1871523017666181115104159
|View full text |Cite
|
Sign up to set email alerts
|

Development of Betamethasone Dipropionate-Loaded Nanostructured Lipid Carriers for Topical and Transdermal Delivery

Abstract: Introduction: Betamethasone dipropionate is a highly effective corticosteroid anti-inflammatory. However, the main drawback of its topical use is the limited skin penetration into deeper skin layers. Also, its systemic use has shown many side effects. </P><P> Objective: The goal of this research was to formulate betamethasone dipropionate in nanostructured lipid carriers (NLC) formulae that contain oleic acid to aid its penetration to deeper skin layers and to aid absorption to local regions upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…As explained by Edwards et al [ 4 ], this is observed as a reduction in the obtained melting enthalpies. Expectedly, all the films started to melt at lower points when compared to their pure ingredients, which is partly attributed to differences in the specific film surface areas available for testing [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…As explained by Edwards et al [ 4 ], this is observed as a reduction in the obtained melting enthalpies. Expectedly, all the films started to melt at lower points when compared to their pure ingredients, which is partly attributed to differences in the specific film surface areas available for testing [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NLC was prepared by high shear homogenization followed by the sonication method and was shown to penetrate more efficiently into the skin layers as compared to a traditional cream. Further, NLC formulations that comprised a higher percentage of oleic acid showed higher penetration through the skin [ 128 ].…”
Section: Lipid-based Nanocarrier System For Skin Deliverymentioning
confidence: 99%
“…( Dasht Bozorg et al, 2022 ). For some locally effective drugs, compared with oral and injection routes, topical transdermal administration can reduce the entry of drugs into the blood circulation, thereby reducing systemic adverse reactions ( Hanna et al, 2019 ). Besides, the slow release of topical drugs into the skin tissue can prolong the efficacy time, reduce the number of doses, provide patients with greater comfort ( Jiang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%